MOFs-derived prismatic nitrogen-doped porous carbon material, preparation method and application of MOFs-derived prismatic nitrogen-doped porous carbon material in sodium-sulfur battery

The MOFs-derived prism nitrogen-doped porous carbon material was prepared by solvent-heat method and high-temperature calcination heat treatment method, which solved the problem of slow reaction kinetics and electrode structure collapse in room-temperature sodium-sulfur batteries, and achieved efficient sodium storage performance and cycling stability.

CN119725540APending Publication Date: 2025-03-28GUANGDONG CARBON LANGUAGE NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411910191.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Room temperature sodium-sulfur batteries face the problems of slow kinetics of sulfur conversion to sodium sulfide, collapse of electrode structure, and easy soluble high-order sodium sulfide intermediates, which limit their energy storage performance.

Method used

The MOFs-derived prism nitrogen-doped porous carbon material was prepared by solvothermal method combined with high-temperature calcination heat treatment, as the positive electrode material of sodium-sulfur batteries to improve electrochemical performance and sodium storage performance.

Benefits of technology

The prepared prism nitrogen-doped porous carbon material has a high specific surface area, excellent pore structure and good electrochemical properties, which significantly improves the energy storage performance and cycle stability of sodium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725540A_ABST
    Figure CN119725540A_ABST
Patent Text Reader

Abstract

The invention provides an MOFs derived prismatic nitrogen-doped porous carbon material, a preparation method and application of the MOFs derived prismatic nitrogen-doped porous carbon material in a sodium-sulfur battery, and relates to the technical field of sodium-sulfur batteries. The nitrogen-doped porous carbon material obtained by the invention is prism-shaped, the length is 0.2-5 microns, and the thickness is 0.1-1 micron. The prismatic nitrogen-doped porous carbon material is synthesized by combining a solvothermal method with a high-temperature calcination heat treatment method, and the prismatic nitrogen-doped porous carbon material prepared by the method has high specific surface area, excellent pore structure and good electrochemical performance; the carbon material has potential application in sodium storage performance of a sulfur positive electrode material in a room-temperature sodium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium-sulfur batteries, and particularly relates to a MOFs-derived prismatic nitrogen-doped porous carbon material, a preparation method thereof, and an application thereof in sodium-sulfur batteries. Background Art

[0002] The rapid development of smart grids and electric vehicles has put forward higher requirements for energy storage systems, and there is an urgent need for new energy storage solutions with long lifespan, rich resources, and high energy density. Room temperature sodium-sulfur (RT Na-S) batteries, with advantages such as low cost, high theoretical specific capacity, and environmental friendliness, are regarded as strong candidates for the next-generation energy storage technology. However, RT Na-S batteries still face several technical bottlenecks: one is the sluggish reaction kinetics of sulfur conversion to sodium sulfide, which restricts the reaction rate; the second is that the sulfur electrode undergoes significant volume changes (about 170%) during charge-discharge cycles, resulting in rapid disintegration of the electrode structure and sharp decline in capacity; the third is that higher-order polysulfide (Na2S n , 4 < n ≤ 8) intermediates are easily soluble in the liquid electrolyte and shuttle to the surface of the sodium anode for deposition, causing capacity loss and degradation of interfacial performance.

[0003] To address the above inherent challenges, significant progress has been made in improving the reaction kinetics of RT Na-S by adopting physical adsorption and chemical adsorption strategies. In addition, constructing carbonaceous host materials with diverse structures has been proven to be an efficient electron conduction pathway for enhancing conductivity and effectively suppressing the shuttle effect. As a class of porous crystalline materials formed by the self-assembly of metal ions or clusters and organic ligands through coordination bonds, metal-organic frameworks (MOFs) have characteristics such as high specific surface area, high porosity, structural diversity, and easy regulation, and show broad application prospects in fields such as gas storage and separation, catalysis, fluorescence sensing, and energy storage. In recent years, the research on preparing porous carbon materials using MOFs as precursors has received increasing attention. Porous carbon materials with excellent properties can be obtained by carbonizing MOFs, and these materials have potential application values in energy storage fields such as supercapacitors, lithium-ion batteries, and sodium-sulfur batteries.

[0004] However, traditional porous carbon materials often have problems such as low specific surface area, uneven pore size distribution, and limited electrochemical performance, which restrict their application in high-performance energy storage devices. Nitrogen-doped porous carbon materials can improve the interfacial wettability of the materials and enhance the transport efficiency of electrolyte ions by introducing heteroatom nitrogen, thereby improving the electrochemical performance. In addition, prismatic porous carbon materials, due to their unique morphology and ordered pore structure, are conducive to the rapid transport and storage of ions, further enhancing the electrochemical performance of the materials.

[0005] At present, although there have been some research reports on MOFs-derived porous carbon materials, there are relatively few studies on the preparation of prismatic nitrogen-doped porous carbon materials and their application in room-temperature sodium-sulfur batteries. Therefore, developing an efficient and controllable preparation method for MOFs-derived prismatic nitrogen-doped porous carbon materials and studying their performance in room-temperature sodium-sulfur batteries has important scientific significance and practical application value. Summary of the invention

[0006] The present invention aims to provide a MOFs-derived prismatic nitrogen-doped porous carbon material, a preparation method and application thereof in a sodium-sulfur battery. The prismatic nitrogen-doped porous carbon material prepared by the method has a high specific surface area, an excellent pore structure and good electrochemical properties, and is particularly suitable for energy storage devices such as RT Na-S batteries.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The present invention first provides a method for preparing a MOFs-derived prismatic nitrogen-doped porous carbon material, comprising:

[0009] Step 1: Mix and stir ferric chloride hexahydrate and 2-aminoterephthalic acid, and then put them into a reactor to react to obtain a precursor product MIL-88(B)-NH2;

[0010] Step 2: In an inert gas atmosphere, the precursor product MIL-88(B)-NH2 obtained in step 1 is placed in a tube furnace and calcined at high temperature to obtain a powder material N-Fe3O4@C;

[0011] Step 3: Grind the powder material N-Fe3O4@C obtained in step 3 evenly, then put it into a reactor, add concentrated hydrochloric acid and heat it, and obtain MOFs-derived prismatic nitrogen-doped porous carbon N-MPC by centrifugation, washing and drying.

[0012] Preferably, the molar ratio of ferric chloride hexahydrate to 2-aminoterephthalic acid in step 1 is (1-3): (1-3).

[0013] Preferably, the reaction temperature in step 1 is 100-200° C., and the reaction time is 2-40 h.

[0014] Preferably, the high temperature calcination temperature in step 2 is 300-800°C, the calcination time is 2-20 hours, and the heating rate is 1-10°C min -1 .

[0015] Preferably, the heating temperature in step three is 100-200° C., and the heating time is 2-60 h.

[0016] The present invention also provides a MOFs-derived prismatic nitrogen-doped porous carbon material obtained by the above preparation method, which has a length of 0.2-5 μm and a thickness of 0.1-1 μm.

[0017] The present invention also provides the use of the above MOFs-derived prismatic nitrogen-doped porous carbon material as a positive electrode material in a sodium-sulfur battery.

[0018] Preferably, the application is specifically as follows: the N-MPC obtained above and the sublimated sulfur are evenly ground, placed in a quartz tube, vacuumed and heated, and after complete cooling, the quartz tube is opened and placed in a tubular furnace in an inert gas atmosphere for calcination, and finally a sulfur-loaded N-MPC@S composite positive electrode material is obtained.

[0019] Preferably, the mass ratio of the N-MPC to the sublimated sulfur is 1:1-1:5.

[0020] Preferably, the heating temperature is 80-200° C., and the reaction time is 2-60 hours; the calcination temperature is 100-300° C., and the calcination time is 0.1-1 hour.

[0021] Beneficial effects of the present invention

[0022] The present invention provides a MOFs-derived prismatic nitrogen-doped porous carbon material, a preparation method and an application thereof in a sodium-sulfur battery. The obtained nitrogen-doped porous carbon material is prismatic, with a length of 0.2-5 μm and a thickness of 0.1-1 μm. The present invention synthesizes a prismatic nitrogen-doped porous carbon material by combining a solvent thermal method with a high-temperature calcination heat treatment method. The prismatic nitrogen-doped porous carbon material prepared by the method has a high specific surface area, an excellent pore structure and good electrochemical properties. The carbon material has potential application in the sodium storage performance of a sulfur positive electrode material in a room temperature sodium-sulfur battery. Moreover, the synthesis method of the present invention is simple, green and pollution-free, and reduces costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Transmission electron microscope photograph and scanning electron microscope photograph of the MOFs-derived prismatic nitrogen-doped porous carbon prepared in Example 1;

[0024] Figure 2 X-ray diffraction spectra of MIL-88(Fe)-NH2, N-Fe3O4@C and N-MPC prepared in Example 1;

[0025] Figure 3 This is a thermogravimetric analysis curve of the sulfur-loaded N-MPC@S composite cathode material prepared in Example 1;

[0026] Figure 4 The nitrogen adsorption-desorption isotherm curves and pore size distribution diagrams of N-MPC and N-MPC@S prepared in Example 1;

[0027] Figure 5 The XPS spectrum of N-MPC prepared in Example 1;

[0028] Figure 6 The N-MPC@S prepared in Example 1 was scanned at a rate of 0.1 mV s -1 CV curve when

[0029] Figure 7 The rate performance diagram of N-MPC@S prepared in Example 1 at different current densities;

[0030] Figure 8 This is the cycling performance diagram of N-MPC@S prepared in Example 1 at different current densities. DETAILED DESCRIPTION

[0031] The present invention first provides a method for preparing a MOFs-derived prismatic nitrogen-doped porous carbon material, comprising:

[0032] Step 1: Mix and stir ferric chloride hexahydrate and 2-aminoterephthalic acid. Preferably, the mixing comprises first dissolving ferric chloride hexahydrate in a solvent, and the solvent is preferably N,N-dimethylformamide. After stirring and dissolving, 2-aminoterephthalic acid (PTA-NH2) is added. After continuing to stir and dissolve, the solution becomes dark brown. The mixture is then loaded into a polytetrafluoroethylene-lined autoclave, and the stainless steel autoclave shell lid is tightened. The mixture is placed in a blast oven for heating and reaction. The reaction temperature is preferably 100-200°C, and the reaction time is preferably 2-40h. After the reaction is completed, the obtained brown solution is collected by centrifugation. The product after centrifugation is preferably washed three times each with deionized water and anhydrous ethanol alternately. The product is dried in an oven to obtain a precursor product MIL-88(B)-NH2. The molar ratio of ferric chloride hexahydrate to 2-aminoterephthalic acid is preferably (1-3): (1-3).

[0033] Step 2: In an inert gas atmosphere, the precursor product MIL-88(B)-NH2 obtained in step 1 is placed in a tube furnace and calcined at high temperature to obtain a powder material N-Fe3O4@C; the high temperature calcination temperature is preferably 300-800°C, the calcination time is preferably 2-20 hours, and the heating rate is preferably 1-10°C min -1 .

[0034] Step 3: Grind the powder material N-Fe3O4@C obtained in step 3 evenly, then put it into a reactor, add concentrated hydrochloric acid and heat it. The heating temperature is preferably 100-200°C, and the heating time is preferably 2-60h. After the reactor is completely cooled, the product is collected by centrifugation. The product is preferably washed with deionized water to pH = 7, and finally washed with anhydrous ethanol to obtain MOFs-derived prismatic nitrogen-doped porous carbon N-MPC; wherein the mass g of the powder material N-Fe3O4@C: the volume mL of concentrated hydrochloric acid is preferably 1: (10-40).

[0035] The present invention also provides a MOFs-derived prismatic nitrogen-doped porous carbon material obtained by the above preparation method, which has a length of 0.2-5 μm and a thickness of 0.1-1 μm.

[0036] The present invention also provides the use of the above MOFs-derived prismatic nitrogen-doped porous carbon material as a positive electrode material in a sodium-sulfur battery.

[0037] The method for preparing a positive electrode material from MOFs-derived prismatic nitrogen-doped porous carbon material preferably comprises:

[0038] The N-MPC and sublimated sulfur prepared above are ground evenly and then loaded into a quartz tube. The tube is evacuated and both ends are sealed. The loaded quartz tube is placed in an oven for heating. After it is completely cooled, the quartz tube is opened and placed in a tubular furnace in an inert gas atmosphere for calcination, and finally a sulfur-loaded N-MPC@S composite positive electrode material is obtained.

[0039] The mass ratio of the N-MPC to the sublimated sulfur is preferably 1:1-1:5, the reaction temperature in the oven is preferably 80-200°C, the reaction time is preferably 2-60 hours, the calcination in the tubular furnace is carried out under the protection of an inert gas such as nitrogen or argon, the calcination temperature is preferably 100-300°C, and the calcination time is preferably 0.1-1 hour.

[0040] The present invention is further described in detail below with reference to specific examples, in which the raw materials involved are all commercially available.

[0041] Example 1

[0042] a. Use a measuring cylinder to measure 30 mL of N,N-dimethylformamide, add 1 mmol of ferric chloride hexahydrate (FeCl3.6H2O) and stir until completely dissolved, then add 1 mmol of 2-aminoterephthalic acid (PTA-NH2), continue stirring for 0.5 h, and the solution will turn dark brown after dissolution. Then put it into a high-pressure reactor lined with polytetrafluoroethylene, tighten the stainless steel reactor shell lid, and heat it in a blast oven. Heat the reaction at a constant temperature of 120°C for 8 h.

[0043] b. Collect the brown solution obtained in step a by centrifugation, wash the product after centrifugation three times with deionized water and anhydrous ethanol alternately, and dry the product in an oven to obtain a brown product MIL-88(B)-NH2.

[0044] c. The product MIL-88(B)-NH2 obtained in step b was calcined at 650°C for 2h in a tube furnace in an inert gas atmosphere, with a calcination heating rate of 2°C min -1 , and finally N-Fe3O4@C black powder material was obtained.

[0045] d. Grind the black powder obtained in step c evenly, then weigh 1 g and put it into a 40 mL reactor, add 10 mL of concentrated hydrochloric acid, heat it in an oven at 120 ° C for 48 h, and collect the product by centrifugation after the reactor is completely cooled. Wash the product with deionized water to pH = 7, and finally wash it with anhydrous ethanol, and put it into an oven to dry overnight to obtain MOFs-derived prismatic nitrogen-doped porous carbon (N-MPC).

[0046] e. Grind 0.1 g of N-MPC and 0.1 g of sublimated sulfur obtained in step d evenly, and then put them into a quartz tube, evacuate the tube and seal both ends. Put the assembled quartz tube into an oven and heat it at 155° C. for 15 h. After it is completely cooled, open the quartz tube and put it into a tubular furnace in an inert gas atmosphere and calcine it at 200° C. for 0.5 h, and finally obtain the sulfur-loaded N-MPC@S composite positive electrode material.

[0047] Figure 1 The transmission electron microscope image and scanning electron microscope image of the MOFs-derived prismatic nitrogen-doped porous carbon prepared in Example 1 are shown in FIG. Figure 1 a is a scanning electron microscope photo of MIL-88(Fe)-NH2; Figure 1 b is the transmission electron microscope photo of MIL-88(Fe)-NH2. Figure 1 c is the SEM photo of N-Fe3O4@C; Figure 1 d is the transmission electron microscope photo of N-Fe3O4@C. Figure 1 e is the scanning electron microscope photo of N-MPC; Figure 1 f is the transmission electron microscopy photograph of N-MPC. Figure 1 The SEM and TEM images clearly reveal that the prepared N-MPC inherits the prismatic morphology of the precursor MIL-88(Fe)-NH2. The TEM image further reveals the hierarchical porous structure inside the N-MPC. This structural feature not only provides a physical barrier to effectively curb the shuttle effect of polysulfides, but also greatly promotes the deep penetration of the electrolyte, thereby significantly improving the ion transmission rate in the material.

[0048] Figure 2X-ray diffraction spectra of MIL-88(Fe)-NH2, N-Fe3O4@C and N-MPC prepared in Example 1. Figure 2 This indicates that the N-MPC obtained by acid etching only has a broad peak marked by amorphous carbon near 20°.

[0049] Figure 3 This is the thermogravimetric analysis curve of the sulfur-loaded N-MPC@S composite cathode material prepared in Example 1. Figure 3 This indicates that after 150°C, due to reaching the boiling point of sulfur, elemental sulfur evaporates and loses, reaching a maximum value at around 250°C. Most of the sulfur is completely lost before 300°C, and the small amount of mass loss after that is caused by the volatilization of sulfur that diffuses into the micropores. After calculation, the sulfur loading of N-MPC@S is about 44.5%.

[0050] Figure 4 The nitrogen adsorption-desorption isotherm curves and pore size distribution diagrams of N-MPC and N-MPC@S prepared in Example 1 are shown in FIG. Figure 4 a is the nitrogen adsorption-desorption isotherms of N-MPC and N-MPC@S; Figure 4 b is the pore size distribution diagram of N-MPC and N-MPC@S. Figure 4 a shows that the specific surface area of ​​N-MPC reaches 225m 2 g -1 After being combined with sulfur, the specific surface area of ​​N-MPC@S rapidly dropped to only 9 m 2 g -1 . Figure 4 b shows that before compounding with sulfur, the pore size is mainly distributed in the micropore and mesopore sizes; after compounding with sulfur, the micropore part completely disappears and the number of mesopores is significantly reduced, indicating that during the compounding process, sulfur enters the micropores and mesopores, achieving the function of storing sulfur.

[0051] Figure 5 This is the XPS spectrum of N-MPC prepared in Example 1, where Figure 5 a is the full XPS spectrum; Figure 5 b is the C1s high-resolution spectrum; Figure 5 c is the high-resolution spectrum of N1s; Figure 5 d is the O1s high-resolution spectrum. Figure 5This shows that the full spectrum can determine the presence of carbon, nitrogen, and oxygen. The high-resolution spectrum of C1s has three peaks at 287.3, 284.8, and 283.9 eV, corresponding to C=O, CO, and CC bonds. The high-resolution spectrum of N 1s divides nitrogen into three types, namely, oxidized nitrogen (404 eV), pyrrolic nitrogen (399.8 eV), and pyridinic nitrogen (397.5 eV). The high-resolution spectrum of O 1s can determine that the peaks at 532.5, 531.3, and 530.1 eV correspond to CO, C=O, and Fe3O4, respectively.

[0052] Figure 6 The N-MPC@S prepared in Example 1 was scanned at a rate of 0.1 mV s -1 CV curve when . Figure 6 It shows that there is an obvious reduction peak at 0.75V in the first cycle, and then it stabilizes at 0.9V due to the side reaction caused by the formation of SEI film. In the subsequent scanning process, four reduction peaks appeared at 2.0, 1.6, 1.2 and 0.9V respectively during the reduction process. The reduction reaction at 2.0V corresponds to the conversion of S8 to Na2S8; the reduction peaks at 1.6V and 1.2V correspond to the conversion of Na2S4 to various short-chain polysulfides (Na2S x , 2≤x≤4), is very stable in the CV scan, indicating that the reaction continues to occur stably in the subsequent cycle process; the reduction peak at 0.9V corresponds to the conversion from Na2S2 to Na2S. The oxidation peak at 1.5V corresponds to the conversion of various short-chain polysulfides to Na2S4, and the oxidation peak at 1.7V corresponds to the conversion of Na2S4 to Na2S8. The oxidation peak signal here is obviously weaker due to the faster kinetic process in the ether electrolyte. The oxidation peak that appears at about 2.2V corresponds to the reaction from Na2S8 to S8. The subsequent stability and the overlap of the corresponding reaction peaks indicate that the electrochemical reaction process in this system is completely reversible.

[0053] Figure 7 The rate performance of N-MPC@S prepared in Example 1 at different current densities. Figure 7 It shows that N-MPC@S has a high current density from 0.05A g -1 , 0.1A g -1 , 0.2A g -1 , 0.5A g -1 , 1A g -1 , 2A g -1 , and then return to 0.05A g -1The discharge capacity diagram during the process. During this process, as the current density increases, the discharge capacity decreases. This is because the faster kinetic process under high current may cause the electrochemical reaction to be incomplete, resulting in lower capacity. The average capacity during this process reached 1452, 1192, 1063, 962, 868, 744, 861, 955, 1040, 1102, and 1142 mAh g, respectively. -1 Except for the first few cycles, due to the production of a small amount of soluble intermediates, the subsequent cycles showed excellent rate performance, indicating that the prepared N-MPC@S composite material has excellent performance in adapting to continuously changing current density.

[0054] Figure 8 The cycle performance diagram of N-MPC@S prepared in Example 1 at different current densities, where Figure 8 a is 100mAg -1 Cycling performance at current density, Figure 8 b is 1A g -1 Cycling performance at different current densities. Figure 8 Description: At 100mA g -1 After 50 cycles at a current density of 1000 mA hg -1 At 1A g -1 At this current density, the capacity is still 850 mA hg after 350 cycles. -1 During the cycle, the capacity remains stable.

[0055] Example 2

[0056] a. Use a measuring cylinder to measure 30 mL of N,N-dimethylformamide, add 1 mmol of ferric chloride hexahydrate (FeCl3.6H2O) and stir until completely dissolved, then add 2 mmol of 2-aminoterephthalic acid (PTA-NH2), continue stirring for 0.5 h, and the solution will turn dark brown after dissolution. Then put it into a high-pressure reactor lined with polytetrafluoroethylene, tighten the stainless steel reactor shell lid, and heat it in a blast oven. Heat it at a constant temperature of 120°C for 8 h.

[0057] b. Collect the brown solution obtained in step a by centrifugation, wash the product after centrifugation three times with deionized water and anhydrous ethanol alternately, and dry the product in an oven to obtain a brown product MIL-88(B)-NH2.

[0058] c. The product MIL-88(B)-NH2 obtained in step b was calcined at 650°C for 2h in a tube furnace in an inert gas atmosphere, with a calcination heating rate of 2°C min -1 , and finally N-Fe3O4@C black powder material was obtained.

[0059] d. Grind the black powder obtained in step c evenly, then weigh 1 g and put it into a 40 mL reactor, add 10 mL of concentrated hydrochloric acid, heat it in an oven at 120 ° C for 48 h, and collect the product by centrifugation after the reactor is completely cooled. Wash the product with deionized water to pH = 7, and finally wash it with anhydrous ethanol, and put it into an oven to dry overnight to obtain MOFs-derived prismatic nitrogen-doped porous carbon (N-MPC).

[0060] e. Grind 0.1 g of N-MPC and 0.1 g of sublimated sulfur obtained in step d evenly, and then put them into a quartz tube, evacuate the tube and seal both ends. Put the assembled quartz tube into an oven and heat it at 155° C. for 15 h. After it is completely cooled, open the quartz tube and put it into a tubular furnace in an inert gas atmosphere and calcine it at 200° C. for 0.5 h, and finally obtain the sulfur-loaded N-MPC@S composite positive electrode material.

[0061] Example 3

[0062] a. Use a measuring cylinder to measure 30 mL of N,N-dimethylformamide, add 1 mmol of ferric chloride hexahydrate (FeCl3.6H2O) and stir until completely dissolved, then add 1 mmol of 2-aminoterephthalic acid (PTA-NH2), continue stirring for 0.5 h, and the solution will turn dark brown after dissolution. Then put it into a high-pressure reactor lined with polytetrafluoroethylene, tighten the stainless steel reactor shell lid, and heat it in a blast oven. Heat the reaction at a constant temperature of 140°C for 8 h.

[0063] b. Collect the brown solution obtained in step a by centrifugation, wash the product after centrifugation three times with deionized water and anhydrous ethanol alternately, and dry the product in an oven to obtain a brown product MIL-88(B)-NH2.

[0064] c. The product MIL-88(B)-NH2 obtained in step b was calcined at 650°C for 2h in a tube furnace in an inert gas atmosphere, with a calcination heating rate of 2°C min -1 , and finally N-Fe3O4@C black powder material was obtained.

[0065] d. Grind the black powder obtained in step c evenly, then weigh 1 g and put it into a 40 mL reactor, add 10 mL of concentrated hydrochloric acid, heat it in an oven at 120 ° C for 48 h, and collect the product by centrifugation after the reactor is completely cooled. Wash the product with deionized water to pH = 7, and finally wash it with anhydrous ethanol, and put it into an oven to dry overnight to obtain MOFs-derived prismatic nitrogen-doped porous carbon (N-MPC).

[0066] e. Grind 0.1 g of N-MPC and 0.1 g of sublimated sulfur obtained in step d evenly, and then put them into a quartz tube, evacuate the tube and seal both ends. Put the assembled quartz tube into an oven and heat it at 155° C. for 15 h. After it is completely cooled, open the quartz tube and put it into a tubular furnace in an inert gas atmosphere and calcine it at 200° C. for 0.5 h, and finally obtain the sulfur-loaded N-MPC@S composite positive electrode material.

[0067] Example 4

[0068] a. Use a measuring cylinder to measure 30 mL of N,N-dimethylformamide, add 1 mmol of ferric chloride hexahydrate (FeCl3.6H2O) and stir until completely dissolved, then add 2 mmol of 2-aminoterephthalic acid (PTA-NH2), continue stirring for 0.5 h, and the solution will turn dark brown after dissolution. Then put it into a high-pressure reactor lined with polytetrafluoroethylene, tighten the stainless steel reactor shell lid, and heat it in a blast oven. Heat the reaction at a constant temperature of 160°C for 8 h.

[0069] b. Collect the brown solution obtained in step a by centrifugation, wash the product after centrifugation three times with deionized water and anhydrous ethanol alternately, and dry the product in an oven to obtain a brown product MIL-88(B)-NH2.

[0070] c. The product MIL-88(B)-NH2 obtained in step b was calcined at 650°C for 2h in a tube furnace in an inert gas atmosphere, with a calcination heating rate of 2°C min -1 , and finally N-Fe3O4@C black powder material was obtained.

[0071] d. Grind the black powder obtained in step c evenly, then weigh 1 g and put it into a 40 mL reactor, add 10 mL of concentrated hydrochloric acid, heat it in an oven at 120 ° C for 48 h, and collect the product by centrifugation after the reactor is completely cooled. Wash the product with deionized water to pH = 7, and finally wash it with anhydrous ethanol, and put it into an oven to dry overnight to obtain MOFs-derived prismatic nitrogen-doped porous carbon (N-MPC).

[0072] e. Grind 0.1 g of N-MPC and 0.1 g of sublimated sulfur obtained in step d evenly, and then put them into a quartz tube, evacuate the tube and seal both ends. Put the assembled quartz tube into an oven and heat it at 155° C. for 15 h. After it is completely cooled, open the quartz tube and put it into a tubular furnace in an inert gas atmosphere and calcine it at 200° C. for 0.5 h, and finally obtain the sulfur-loaded N-MPC@S composite positive electrode material.

[0073] Example 5

[0074] a. Use a measuring cylinder to measure 30 mL of N,N-dimethylformamide, add 1 mmol of ferric chloride hexahydrate (FeCl3.6H2O) and stir until completely dissolved, then add 2 mmol of 2-aminoterephthalic acid (PTA-NH2), continue stirring for 0.5 h, and the solution will turn dark brown after dissolution. Then put it into a high-pressure reactor lined with polytetrafluoroethylene, tighten the stainless steel reactor shell lid, and heat it in a blast oven. Heat the reaction at a constant temperature of 120°C for 10 h.

[0075] b. Collect the brown solution obtained in step a by centrifugation, wash the product after centrifugation three times with deionized water and anhydrous ethanol alternately, and dry the product in an oven to obtain a brown product MIL-88(B)-NH2.

[0076] c. The product MIL-88(B)-NH2 obtained in step b was calcined at 650°C for 2h in a tube furnace in an inert gas atmosphere, with a calcination heating rate of 2°C min -1 , and finally N-Fe3O4@C black powder material was obtained.

[0077] d. Grind the black powder obtained in step c evenly, then weigh 1 g and put it into a 40 mL reactor, add 10 mL of concentrated hydrochloric acid, heat it in an oven at 120 ° C for 48 h, and collect the product by centrifugation after the reactor is completely cooled. Wash the product with deionized water to pH = 7, and finally wash it with anhydrous ethanol, and put it into an oven to dry overnight to obtain MOFs-derived prismatic nitrogen-doped porous carbon (N-MPC).

[0078] e. Grind 0.1 g of N-MPC and 0.1 g of sublimated sulfur obtained in step d evenly, and then put them into a quartz tube, evacuate the tube and seal both ends. Put the assembled quartz tube into an oven and heat it at 155° C. for 15 h. After it is completely cooled, open the quartz tube and put it into a tubular furnace in an inert gas atmosphere and calcine it at 200° C. for 0.5 h, and finally obtain the sulfur-loaded N-MPC@S composite positive electrode material.

[0079] Example 6

[0080] a. Use a measuring cylinder to measure 30 mL of N,N-dimethylformamide, add 1 mmol of ferric chloride hexahydrate (FeCl3.6H2O) and stir until completely dissolved, then add 2 mmol of 2-aminoterephthalic acid (PTA-NH2), continue stirring for 0.5 h, and the solution will turn dark brown after dissolution. Then put it into a high-pressure reactor lined with polytetrafluoroethylene, tighten the stainless steel reactor shell lid, and heat it in a blast oven. Heat the reaction at a constant temperature of 180°C for 8 h.

[0081] b. Collect the brown solution obtained in step a by centrifugation, wash the product after centrifugation three times with deionized water and anhydrous ethanol alternately, and dry the product in an oven to obtain a brown product MIL-88(B)-NH2.

[0082] c. The product MIL-88(B)-NH2 obtained in step b was calcined at 650°C for 2h in a tube furnace in an inert gas atmosphere, with a calcination heating rate of 2°C min -1 , and finally N-Fe3O4@C black powder material was obtained.

[0083] d. Grind the black powder obtained in step c evenly, then weigh 1 g and put it into a 40 mL reactor, add 10 mL of concentrated hydrochloric acid, heat it in an oven at 120 ° C for 48 h, and collect the product by centrifugation after the reactor is completely cooled. Wash the product with deionized water to pH = 7, and finally wash it with anhydrous ethanol, and put it into an oven to dry overnight to obtain MOFs-derived prismatic nitrogen-doped porous carbon (N-MPC).

[0084] e. Grind 0.1 g of N-MPC and 0.1 g of sublimated sulfur obtained in step d evenly, and then put them into a quartz tube, evacuate the tube and seal both ends. Put the assembled quartz tube into an oven and heat it at 155° C. for 15 h. After it is completely cooled, open the quartz tube and put it into a tubular furnace in an inert gas atmosphere and calcine it at 200° C. for 0.5 h, and finally obtain the sulfur-loaded N-MPC@S composite positive electrode material.

[0085] Example 7

[0086] a. Use a measuring cylinder to measure 30 mL of N,N-dimethylformamide, add 1 mmol of ferric chloride hexahydrate (FeCl3.6H2O) and stir until completely dissolved, then add 2 mmol of 2-aminoterephthalic acid (PTA-NH2), continue stirring for 0.5 h, and the solution will turn dark brown after dissolution. Then put it into a high-pressure reactor lined with polytetrafluoroethylene, tighten the stainless steel reactor shell lid, and heat it in a blast oven. Heat it at a constant temperature of 120°C for 8 h.

[0087] b. Collect the brown solution obtained in step a by centrifugation, wash the product after centrifugation three times with deionized water and anhydrous ethanol alternately, and dry the product in an oven to obtain a brown product MIL-88(B)-NH2.

[0088] c. The product MIL-88(B)-NH2 obtained in step b was calcined at 650°C for 2h in a tube furnace in an inert gas atmosphere, with a calcination heating rate of 2°C min -1 , and finally N-Fe3O4@C black powder material was obtained.

[0089] d. Grind the black powder obtained in step c evenly, then weigh 1 g and put it into a 40 mL reactor, add 20 mL of concentrated hydrochloric acid, heat it in an oven at 120 ° C for 48 h, and collect the product by centrifugation after the reactor is completely cooled. Wash the product with deionized water to pH = 7, and finally wash it with anhydrous ethanol, and put it into an oven to dry overnight to obtain MOFs-derived prismatic nitrogen-doped porous carbon (N-MPC).

[0090] e. Grind 0.1 g of N-MPC and 0.1 g of sublimated sulfur obtained in step d evenly, and then put them into a quartz tube, evacuate the tube and seal both ends. Put the assembled quartz tube into an oven and heat it at 155° C. for 15 h. After it is completely cooled, open the quartz tube and put it into a tubular furnace in an inert gas atmosphere and calcine it at 200° C. for 0.5 h, and finally obtain the sulfur-loaded N-MPC@S composite positive electrode material.

[0091] Example 8

[0092] a. Use a measuring cylinder to measure 30 mL of N,N-dimethylformamide, add 1 mmol of ferric chloride hexahydrate (FeCl3.6H2O) and stir until completely dissolved, then add 2 mmol of 2-aminoterephthalic acid (PTA-NH2), continue stirring for 0.5 h, and the solution will turn dark brown after dissolution. Then put it into a high-pressure reactor lined with polytetrafluoroethylene, tighten the stainless steel reactor shell lid, and heat it in a blast oven. Heat it at a constant temperature of 120°C for 8 h.

[0093] b. Collect the brown solution obtained in step a by centrifugation, wash the product after centrifugation three times with deionized water and anhydrous ethanol alternately, and dry the product in an oven to obtain a brown product MIL-88(B)-NH2.

[0094] c. The product MIL-88(B)-NH2 obtained in step b was calcined at 650°C for 2h in a tube furnace in an inert gas atmosphere, with a calcination heating rate of 2°C min -1 , and finally N-Fe3O4@C black powder material was obtained.

[0095] d. Grind the black powder obtained in step c evenly, then weigh 1 g and put it into a 40 mL reactor, add 30 mL of concentrated hydrochloric acid, heat it in an oven at 120 ° C for 48 h, and collect the product by centrifugation after the reactor is completely cooled. Wash the product with deionized water to pH = 7, and finally wash it with anhydrous ethanol, and put it into an oven to dry overnight to obtain MOFs-derived prismatic nitrogen-doped porous carbon (N-MPC).

[0096] e. Grind 0.1 g of N-MPC and 0.1 g of sublimated sulfur obtained in step d evenly, and then put them into a quartz tube, evacuate the tube and seal both ends. Put the assembled quartz tube into an oven and heat it at 155° C. for 15 h. After it is completely cooled, open the quartz tube and put it into a tubular furnace in an inert gas atmosphere and calcine it at 200° C. for 0.5 h, and finally obtain the sulfur-loaded N-MPC@S composite positive electrode material.

[0097] The present invention is not limited to the above embodiments, and any replacements, improvements, etc. made within the technical scope of the present embodiment belong to the protection scope of the present invention.

Claims

1. A method for preparing a MOFs-derived prismatic nitrogen-doped porous carbon material, characterized in that: include: Step 1: Mix and stir ferric chloride hexahydrate and 2-aminoterephthalic acid, and then put them into a reactor to react to obtain a precursor product MIL-88(B)-NH2; Step 2: In an inert gas atmosphere, the precursor product MIL-88(B)-NH2 obtained in step 1 is placed in a tube furnace and calcined at high temperature to obtain a powder material N-Fe3O4@C; Step 3: Grind the powder material N-Fe3O4@C obtained in step 3 evenly, then put it into a reactor, add concentrated hydrochloric acid and heat it, and obtain MOFs-derived prismatic nitrogen-doped porous carbon N-MPC by centrifugation, washing and drying.

2. The method for preparing a MOFs-derived prismatic nitrogen-doped porous carbon material according to claim 1, characterized in that: The molar ratio of ferric chloride hexahydrate to 2-aminoterephthalic acid in step 1 is (1-3): (1-3).

3. The method for preparing a MOFs-derived prismatic nitrogen-doped porous carbon material according to claim 1, characterized in that: The reaction temperature in step 1 is 100-200° C., and the reaction time is 2-40 hours.

4. The method for preparing a MOFs-derived prismatic nitrogen-doped porous carbon material according to claim 1, characterized in that: The high temperature calcination temperature in step 2 is 300-800°C, the calcination time is 2-20 hours, and the heating rate is 1-10°C min -1 .

5. The method for preparing a MOFs-derived prismatic nitrogen-doped porous carbon material according to claim 1, characterized in that: The heating temperature in step 3 is 100-200° C., and the heating time is 2-60 hours.

6. The MOFs-derived prismatic nitrogen-doped porous carbon material obtained by the preparation method according to claim 1, characterized in that: The length is 0.2-5μm and the thickness is 0.1-1μm.

7. Use of the MOFs-derived prismatic nitrogen-doped porous carbon material as claimed in claim 6 as a positive electrode material in a sodium-sulfur battery.

8. The use according to claim 7, characterized in that: The application is specifically as follows: the N-MPC obtained above and the sublimated sulfur are evenly ground, placed in a quartz tube, vacuumed and heated, and after complete cooling, the quartz tube is opened and placed in a tubular furnace in an inert gas atmosphere for calcination, and finally a sulfur-loaded N-MPC@S composite positive electrode material is obtained.

9. The use according to claim 8, characterized in that: The mass ratio of the N-MPC to the sublimated sulfur is 1:1-1:

5.

10. The use according to claim 8, characterized in that: The heating temperature is 80-200°C, the reaction time is 2-60h; the calcination temperature is 100-300°C, and the calcination time is 0.1-1h.